Kemajuan Teknologi dan Isu Etika dalam Pendidikan Islam - Juli Ahirin; Sukarsih Sukarsih; Idaya Andriani3 Gafar Alamsya; Fakhruddin Fakhruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore and examine information that analyzes technological advances and emerging issues related to their impact on ethics in Islamic education. The method used is a literature review by analyzing sources or data from scientific journals on topics relevant to the research. The research results show that the presence of technology is very helpful and makes daily activities easier, including supporting various activities in the educational sector. However, if used unwisely, technology can cause user ethics to decline. Islamic education is a solution in dealing with this problem through implementing learning based on Islamic methods and enforcing an Islamic education system to form good faith and character. Keywords: Ethics, Issues, Islamic Education, Technology